Targeted Molecular Design of Functionalized Fullerenes for High‐Performance and Stable Perovskite Solar Cells. Issue 6 (6th June 2022) - Xing, Zhou; Li, Shu-Hui; Yang, Shihe
Abstract : Targeted Molecular Design of Functionalized Fullerenes Functionalized fullerenes play crucial roles in promoting power conversion efficiency and stability of perovskite photovoltaics. In article number 2200012, Zhou Xing, Shu‐Hui Li, and Shihe Yang review recent progress in the application of functionalized fullerenes for perovskite solar cells, placing special emphasis on the importance of targeted molecular design of fullerene structures for different application scenarios to meet diverse functional requirements in specific device structures.